Однорезонаторный ускоритель на 1 Мэв для биологических исследований - Диденко А. Н. Андрей Николаевич; Каминская Р. Г.; Осипов В. В.; Уралов Г. А.; Юшков Ю. Г. Юрий Георгиевич (1969, 1969)
Заглавие с титульного листа